Koncepcja genezy i dziejów reformacji „Zawstydzeniu arianów” Piotra Skargi - Szymczak, Dawid (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The subjects of the article are genesis and history of the Reformation in the writings of Piotr Skarga, most fully shown in his polemics with Hieronim Moskorzowski, specifically in the first Abashment of the Arians (1604). An argument with Arian writer is crucial for mentioned issues, because the Royal Preacher derived all factions of the Reformation from one ancestor — Arius. Skarga was relying his historical narration on the marks of the True Church (via notarum). He was convincing that not having any of those marks had direct influence on shaping and existence of the Reformation. An author in his writings therefore was undertaking an issue of history of the heterodox communities, with intention to present it in the specific historiosophical perspective.